(untitled) (Sir Salimullah Medical College Journal, 2022)
The present study was undertaken to evaluate the outcome of peroperative intravenous lidocaine in reducing the intensity of postoperative pain after laparoscopic cholecystectomy.This prospective randomized clinical trial study was conducted in the Department of Anaesthesiology, Sir Salimullah Medical College Mitford Hospital (SSMC MH), Dhaka between April 2014 to September 2014. A total of 80 patients of chronic cholecystitis or cholelithiasis undergoing laparoscopic cholecystectomy in SSMC MH, Dhaka were consecutively included in the study and were randomly assigned to two study groups. Patients in the study group received I/V lidocaine administration @ 3 mg/kg/h and those in the control group received normal saline (0.9% saline) in the same volume by a different observer. When compared the changes in haemodynamic variables from baseline to endpoint of the study shows that there was no significant difference between the groups in terms of heart rate, systolic, diastolic and mean blood pressures except a sudden rise of the parameters at 5 minutes after induction. However, the systolic blood pressure of study group experienced a slight reduction from 30 minutes onwards to the end of the observation and differed significantly from the corresponding SBPs of the control group. The mean BP of both the groups also showed similar trend like systolic BPs.The SpO2 in both study and control groups was maintained at 99 to 100% throughout the study. The study concluded that peroperative infusion of nontoxic dose of lidocaine decreases the intensity of postoperative pain and reduces the postoperative analgesics(inj. Pethidine) requirement without causing any significant adverse effects. Sir Salimullah Med Coll J 2022; 30: 148-154